Fabrication and Characterization of Solid-State Electrochemical Sensor for the Determination of Ni (II) - Timilsina, Rajan; Oli, Haribhakta; Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2017)
available with fulltext.